(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
Nowadays methodology is a special subject, as well as an independent science. On this basis the advanced scientists of foreign countries formulate specific ideas about the methodology of teaching a foreign language, its categories, laws, terms and tasks. The methodology of teaching Russian as a foreign language has developed into an independent academic discipline. There is a rather extensive literature devoted to the issues of teaching Russian as a foreign language. By comprehending the aims and purposes of teaching Russian, philosophy provides a methodological foundation for the methodology of teaching Russian as a foreign language. According to the theory of cognition, the process goes through stages of sensuous and intellectual cognition before being verified in real life. It has long been proven that knowledge of Russian language opens wide opportunities for learning any foreign language, despite the significant differences between them. The norms of the Russian language surprisingly allow us to draw parallels, develop thinking and logic.